Mechanical licensing of the NLRP3 inflammasome in hypertensive vasculature: Integrin mechanotransduction and cytoskeletal control of vascular inflammation - Noof Abdulrahman Alrabiah; Safwan Abid Al-hameed Suliman; Lashin S. Ali; Waseem Ali Hasan; Amany Said Sallam; Rabab S. Hamad; Etedal Ahmed A. Ibrahim; Eman Hamza; Nesreen Elsayed Morsy; Ahmed Shata; Hanan Eissa; Alshaimaa A. Farrag; et al. (Tissue and Cell, 2027)

Histochemical and ultrastructural characterization of the gills in tiger shark, Galeocerdo cuvier (Péron & Lesueur, 1822): Structural strategies for functional adaptation - Fatma A. Madkour; Elsayed S.I. Mohammed; Mohammed Al-Rasheed; Eman E. El-Nahass; Mona M. Elwan; Mohamed Ashour; Roshmon Thomas Mathew; Fatma Abdelhakeem (Tissue and Cell, 2027)

Innovative use of Barley Straw to control algal blooms and improve wastewater quality: Microbial community insights in a sustainable pre-filtration conditioning - Atef Mohamed Gad Mohamed; Ashraf Ahmed; Eman A. Mahmoud; Eman M. Farahat; Khaled N.M. Elsayed; Abeer El Shahawy (Ecological Engineering, 2026)

The interplay of bosentan and finerenone in amelioration of cardiac dysfunction within benign prostatic hyperplasia in rats - Marwa Monier Mahmoud Refaie; Asmaa A. Hasan; Asmaa A. Muhammed; Randa Ahmed Ibrahim; Eman Abdel Naby Hassan; Enas Fathy; Aml Mohamed Soliman; Hoda S. Sherkawy; Olivia N. Beshay; Amr Alam-Eldin Ahmed; Ahmed Ahmed; Samar Hisham Elsayed; et al. (Molecular Biology Reports, 2026)

CD38-driven NAD⁺ depletion governs crypt structure and barrier dysfunction in fluorouracil-induced colonic mucositis: From metabolic collapse to architectural remodeling - Elsayed A. Elmorsy; Rabab S. Hamad; Mohammed Alorini; Attia M. Gabr; Hamad Alsaykhan; Mostafa M. Khodeir; Mohamed F. Hindawy; Abdulaziz A. Alsalloom; Eman Mohamad El Nashar; Ahmed G. Hamad; Haytham Ali; Mohammed Ashraf Ali; et al. (Tissue and Cell, 2026)

VPS13C-mediated endoplasmic reticulum-lysosome tethering in neuronal stress responses - Rabab S. Hamad; Eman Hamza; Ebtehal M. Abdel-Aal; Elsayed A. Elmorsy; Hanan Eissa; Alshaimaa A. Farrag; Ahmed Shata; Ghada M. Nassar; Nesreen Elsayed Morsy; Ahmed A. El-Mansy; Ahmed G. Hamad; Eman R. Abdellatif; et al. (Tissue and Cell, 2026)

Engineering stem cell morphology and tissue architecture through nano-engineered materials - Rabab S. Hamad; Sameh Saber; Elsayed A. Elmorsy; Alshaimaa A. Farrag; Hanan Eissa; Eman Mohamad El Nashar; Norah Saeed Al-Zahrani; Areej M. Alshehri; Mohamed A.M. Ali; Maha M. Amer; Mohamed R. Abdel-Hamed; Enas A. Mohamed; et al. (Tissue and Cell, 2026)

Ultrastructural organization of the neurovascular unit: Nanoscale perspectives on blood-brain barrier architecture - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

Chemical profiling of Salix babylonica leaf extracts using HPLC-ESI-MS and their in-vivo anti-hepatotoxic effect - Eman Abdallah Morsi; Mortada Mohamed Elsayed; El-Sayed Saleh Abdel-Hameed; Ezzat El-Sayed Abdel-Lateef Osman; Tarek Abou-Shousha; Heba Abdel-Hady (South African Journal of Botany, 2026)

Biological effects of statins in systemic sclerosis: a systematic review and meta-analysis of 323 patients - Mostafa A. Khalifa; Hamzah M. Alghzawi; Shehabeldin S. Anan; Ahmad Al Rifai; Ayah A. Anwar; Hayder Ali Raheem Al-Saedi; Eman Awady; Islam Masood; Mohamed Elsayed Badr; Mohamed Ismail; Obada Muayaid; Omar M. Ahmed; et al. (DARU Journal of Pharmaceutical Sciences, 2026)

Corrigendum to : The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells [Tissue Cell, Vol. 101, August 2026, 103431] - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

The nano–biointerface as a structural regulator of cell behavior: Interactions of extracellular vesicles, synthetic nanocarriers, and nanofibers with cells - Rabab S. Hamad; Sameh Saber; Alshaimaa A. Farrag; Hanan Eissa; Elsayed A. Elmorsy; Attalla F. El-kott; Mohammed A. AlShehri; Eman A. Al-Shahari; Waleed Eltantawy; Mohamed A.M. Ali; Anis Ahmad Chaudhary; Ahmed Gaafar; et al. (Tissue and Cell, 2026)

Mitigating surface industrial heat island effects in arid environments: A machine learning approach to sustainable planning - Islam M. Hamdi; Eman Albalawi; Elsayed K. AbdAlmapoed; Sayed R. AbdElaal (Energy and Buildings, 2026)

Culturomics of the plant microbiota: the emerging in situ similis cultivation strategies to meet the complexity of nutritional requirements of microbiota associated with plants of multiple species, growth stages and compartments - Nabil A. Hegazi; Sascha Patz; Florian Fricke; Ayatollah S. El-Zayat; Marwa N. Ahmed; Mervat A. Hamza; Nada A. Moner; Randa M. Abdel-Fatah; Eman H. Nour; Tarek R. Elsayed; Mahmoud S. Abdelwahab; Omar M. Shahat; et al. (Plant and Soil, 2026)
Background The holobiont" refers to the plant and its associated microbiota that are pivotal to the plant's health, fitness, and survival. By in vitro culturing and functionally characterizing members of the plant microbiota, their specific roles in influencing plant responses to environmental changes can be determined and manipulated to foster sustainable agriculture and ecosystem management. Aims The review presents a comprehensive survey and current updates on culturomics of plant microbiota within the overall context of: a) the importance of understanding the plant holobiont composition and functioning; b) the necessity to in vitro track down and explore environmental microbiomes, entailing the plant microbiome with its myriad composition and spatio-temporal dynamics and mobility in various plant species, compartments and growth stages and c) the recent developments of the emerging in-situ similis cultivation strategies grounded on plant-based culture media. Conclusions The review highlights the urgent need to explore in vitro cultivation strategies built on compatible plant-based culture media, and the transformative role of omics technologies in refining these strategies. By bridging fundamental research and cultivation-based applications, such tools offer a gateway towards more sustainable and efficient in vitro cultivation systems, leading to a deeper understanding and potential manipulation of the plant holobiont.

In situ similis culturomic strategies based on vegetable (veggie)-discs extend diversity of in vitro-cultivated microbiota of vegetables - Randa M. Abdel-Fatah; Nada A. Moner; Eman H. Nour; Tarek R. Elsayed; Mohamed T. Abbas; Mahmoud S. Abdelwahab; Mervat A. Hamza; Hanan H. Youssef; Ahmed S. Shehata; Omar M. Shahat; Mohamed Fayez; Silke Ruppel; et al. (Plant and Soil, 2026)

Bridging food and clinical neurotherapeutics in ADHD management: A comprehensive comparative evidence on phytochemicals and non-pharmacologic paradigms - Eman Maher Zahran; Aliaa Gamal; Motaz M. Hassan; Mohamed M. Elsayed; Eyad Y. Elhamadany; Nursin Mustafa Bayoumi; Tarek Gamal Ebrahim; Fatma Alzahraa Mokhtar; Islam M. Abdel-Rahman; Hesham A. Abou-Zied; Usama Ramadan Abdelmohsen (Food Bioscience, 2026)

Exploring topical atorvastatin hyalurosomal gel as an adjuvant for reducing systemic corticosteroid dosage: a randomized clinical trial in severe oral lichen planus patients - Mahitab Elsayed; Aya Essawy; Radwa M. Ismail; Yasmine Gamil; Mohamed G. Hamed; Dalia Elsabaawy; Eman Abdelhakeem; Doaa Hegazy; Radwa M. A. Abd-Elal (Drug Delivery and Translational Research, 2026)
Oral lichen planus (OLP) is a chronic inflammatory disorder with limited topical treatment options and long-term corticosteroid dependency. This study investigates a novel atorvastatin-loaded hyalurosomal gel (ATV-Hyalugel) as a topical adjuvant to reduce systemic corticosteroid use in severe OLP. The objective of the study is to develop, optimize, characterize ATV-Hyalugel and evaluate its clinical efficacy in a randomized controlled clinical trial. ATV-loaded hyalurosomes (ATV-HAs) were prepared via thin-film hydration and optimized using an I-optimal mixture design (independent variables: phospholipid, Tween 80, and hyaluronic acid; responses: entrapment efficiency (EE%), particle size (PS), and zeta potential (ZP). The optimal formulation was incorporated into a chitosan gel, which was characterized for its pH, rheological behavior, and in-vitro drug release. Four weeks randomized controlled trial (n = 90) compared: group one received standard prednisolone (40 mg/day) while group two received half-dose prednisolone (20 mg/day) in combination with ATV-Hyalugel (topically, three times daily). Pain and ulcer scores were recorded weekly. Between-group comparisons were performed using the Mann–Whitney U test (non-parametric; α = 0.05), and within-group improvement from baseline to Week 4 was assessed using the Kruskal–Wallis test. Optimized ATV-HAs demonstrated high EE% (79.1 ± 0.4%), uniform PS (221.2 ± 5.1 nm), and stable ZP (–31.6 ± 0.2 mV). ATV-Hyalugel exhibited mucosa-compatible pH (6.48 ± 0.2), pseudoplastic rheology, and a sustained release profile dominated by diffusion-driven kinetics. Clinically, group two achieved therapeutic equivalence to group one by Week 2 (p > 0.05), despite receiving 50% less corticosteroid. Both groups showed significant symptom reduction from baseline to Week four (p < 0.0001, Kruskal–Wallis). No adverse events were reported with ATV-Hyalugel. ATV-Hyalugel enables a 50% corticosteroid dose reduction while maintaining clinical efficacy. Its favorable release kinetics and safety profile support its use as an innovative adjuvant therapy for severe OLP.

Insights into the stomach of tiger shark, Galeocerdo cuvier (Péron & Lesueur, 1822): Histochemical, ultrastructural, and phylogenetic analysis - Fatma A. Madkour; Elsayed S.I. Mohammed; Eman E. El-Nahass; Mona M. Elwan; Ashraf S. Mohammad; Fatma Abdelhakeem (Tissue and Cell, 2026)

Microbial decontamination and enhanced extraction of value-added compounds from Spirulina platensis using gamma radiation - Hamdy Elsayed Ahmed Ali; Mohamed S. Abd El-AL; Marwa M. Moussa; Ola M. Gomaa; Kamal A. Hassan; Eman A. El-fayoumy (World Journal of Microbiology and Biotechnology, 2026)
Spirulina platensis has garnered increasing attention as a valuable source of proteins, lipids, and pigments, with applications in the food, feed, and nutraceutical industries. However, large-scale cultivation in open pond systems is liable to microbial contamination, posing risks to product quality and productivity. This study evaluated the effects of gamma (γ) irradiation up to 10 kilogray (kGy) as a dual strategy for microbial decontamination and enhanced extraction of bioactive compounds from dried Spirulina powder. A dose of 4 kGy resulted in a substantial reduction in microbial populations, while irradiation at 6 kGy reduced microbial counts to levels below the detection limit of the applied culture-based methods, indicating effective decontamination. The D₁₀-values obtained for Bacillus sp. (0.44 kGy), Staphylococcus aureus (0.41 kGy), and Pseudomonas aeruginosa (0.58 kGy) demonstrate species-dependent radiosensitivity. Analyses using electron spin resonance (ESR), UV–Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), and lipid peroxidation assays demonstrated that γ-irradiation preserved the structural integrity of key biomolecules. Biomass irradiated at 6 kGy exhibited the highest recovery of lipid (60.83 ± 1.38 mg g⁻¹), protein (547.43 ± 2.97 mg g⁻¹), and carbohydrates (275.60 ± 2.50 mg g⁻¹). Pigment extraction also increased, yielding elevated levels of chlorophyll a (11.40 ± 0.10 mg g⁻¹), carotenoids (3.48 ± 0.30 mg g⁻¹), and phycobiliprotein (125.20 ± 0.70 mg g⁻¹). Antioxidant activity peaked at 69.61 ± 1.47% at the same dose, associated with enhanced phenolic content. Overall, γ-irradiation represents a promising biotechnological tool for producing microbiologically safe Spirulina biomass while improving the extraction of value-added bioactive compounds for nutraceutical and pharmaceutical applications.

Scouting the Efficacy of Chitosan-coated Litsea Lipid Carriers Nanoplatform as an Oral Delivery System of Lornoxicam in an Inflammatory Animal Model - Walaa A. El-Dakroury; Abdelrahman R. Said; Gihan F. Asaad; Heba M. I. Abdallah; Marwa E. Shabana; Rahma A. Abdelsalam; Eman M. Elsadek; Basma H. Mohamed; Yara S. Mohamed; Sara M. Seliem; Elsayed Y. Hamada; Belal W. Attef; et al. (Journal of Pharmaceutical Innovation, 2026)
Lornoxicam-loaded chitosan-coated Litsea lipid nanocarriers (LRX-CS-LLCs) were developed as an innovative oral delivery system, combining the synergistic anti-inflammatory effects of Litsea cubeba oil with the mucoadhesive properties of chitosan. The GC/MS analysis of Litsea cubeba oil identified α -citral (47.56%), β -citral (26.86%), and D -limonene (14.00%). Various LRX-loaded LLCs were prepared and optimized. Fourier transform-infrared (FTIR) and differential scanning calorimetry (DSC) confirmed its structural integrity. The optimized (LRX-CS-LLCs) exhibited a particle size of 165.4 ± 6.3 nm, zeta potential of + 26.3 ± 3.2 mV, and entrapment effectiveness of 98.2%. In vitro release followed a controlled kinetic profile. In vivo, LRX-CS-LLCs significantly reduced carrageenan-induced paw edema (77 ± 1.86% inhibition) and PGE2, COX-2, and TNF-α levels by 4.4-, 3.6-, and 3-fold, respectively, compared to the positive control group. Histopathological examinations confirmed normal tissue architecture. Notably, LRX-CS-LLCs outperformed pure-LRX, marketed-LRX, and uncoated-LRX-LLCs, emphasizing its promise as an effective oral therapeutic approach for enhanced management of inflammatory conditions.

Ferric Carboxymaltose Among Patients with Heart Failure and Iron Deficiency: An Updated Meta-Analysis of Randomized Controlled Trials - Ahmed Elmorsy Mohamed; Ahmed Farid Gadelmawla; Zeyad Kholeif; Elsayed Balbaa; Ameer Awashra; Mohamed Elnady; Ahmed Diaa; Mohab Elnashar; Haytham A. M. Dwaik; Eman Mohyeldin; Ranem Afify; Rana Rashwan; et al. (Cardiovascular Toxicology, 2026)

An assessment of safe use and handling of agricultural pesticides by rural women in Abu Homous district of Egypt - Olfat S. Shahin; Atef M. K. Nassar; Nehal Abdel-Hakeem; Eman H. Radwan; Noha Nazeeh; Hafsa O. Hashem; Elsayed E. Hafez; Mamdoh T. Jamal; Zainab Shawky El-khalifa (International Journal of Tropical Insect Science, 2025)

Evaluation of lactoferrin administration as an antibiotic alternative growth promoter: impacts on rabbit’s growth, meat quality, blood biochemical parameters, immune status, antioxidant status, and tissue histology - Tharwat A. Imbabi; Shimaa A. Amer; Eman H. Halawa; Islam I. Sabeq; Abdel-Wahab A. Abdel-Warith; Elsayed M. Younis; Shimaa N. Edris; Simon J. Davies; Lamiaa M. El-Maghraby; Abdalla El-Hadary; Ebrahim Elkhtab; Mohamed H. Abdel Aal; et al. (Tropical Animal Health and Production, 2025)

Evaluation of the role of circular RNA (circ-FAF1) as a diagnostic biomarker for breast cancer in a cohort of Egyptian breast cancer patients - Eman Mohamed Abdellatif; Neamat Elsayed Hegazy; Eman Saad Nassar (Molecular Biology Reports, 2025)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

Electrolyzed water as a microbial control measure for white soft cheese - Salwa M. Awad; Eman F. Abdel-latif; Khalid Sh Tolba; Huda Elsayed; Zeinab I. Ali; Adel M. Saudi (International Dairy Journal, 2025)

Protective role of curcumin and selenium nanoparticles against aluminium chloride-induced hepatorenal toxicity in rats - Safaa M. Awad; Yasser A. Attia; Akaber T. Keshta; Shimaa H. Watad; Eman Rashad; Hassan Elsayed; Shams H. Abdel-Hafez; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Ameliorative potential of dietary supplements, ZnO-K, citrus essential oil, and pumpkin seed oil, on sperm quality in Nile tilapia: Insights from CASA, DNA integrity, antioxidant enzymes, and gene expressions - Marwa M. Ali; Kamal Fathy Elboray; Engy T. Megahed; Hany T. Abu-Taleb; Alshimaa E. Elsayed; Eman Y. Mohammady; Mona S. Amer; Soliman A. Morsi; Eman M. Abbas; Mohamed S. Hassaan; Hosam Elsaied (Fish Physiology and Biochemistry, 2025)
Improving sperm quality is essential for enhancing the reproductive efficiency of Oreochromis niloticus . This study evaluated the effect of three dietary antioxidant supplements, kaolinite-doped zinc oxide (ZnO-K), citrus essential oil (CEO), and pumpkin seed oil (PSO), on sperm quality parameters. A suite of integrative assessments, including Computer-Assisted Semen Analysis (CASA) parameters, spermatozoa DNA integrity, antioxidant enzyme assays, and gene expression profiling, was applied to validate sperm quality. A total of 192 adult males (mean weight 421.31 g ± 30.41 SD) were assigned to four dietary groups, each with three replicates. The control group received a basal diet without supplementation. The experimental groups were fed diets supplemented with ZnO-K (0.06 g kg⁻ 1 ), CEO (10 g kg⁻ 1 ), or PSO (15 g kg⁻ 1 ). ZnO-K supplementation significantly ( P < 0.05) increased milt volume (1.40 ± 0.10 ml) and sperm concentration (5.676 × 10 9 sperm ml −1 ), along with marked improvements in CASA parameters (sperm motility and velocity) and DNA integrity. Antioxidant enzymes, catalase, CAT, glutathione peroxidase, GPX, and superoxide dismutase, SOD, were also significantly elevated in the ZnO-K group, recording activity values of 47.333 ± 1.452 U ml −1 milt, 65.667 ± 5.547 mU ml −1 milt and 60.667 ± 3.382 U ml −1 milt, respectively. Gene expression analysis revealed that CEO induced the highest upregulation of HSP70 , while both CEO and ZnO-K significantly upregulated CC chemokine expression compared to control. In contrast, PSO consistently showed the lowest performance across all measured parameters. Collectively, ZnO-K supplementation most effectively enhanced sperm physiological and biochemical quality, whereas CEO predominantly supported cellular stress protection through gene expression modulation. These findings offered practical implications for optimizing artificial reproduction and sperm cryopreservation strategies in tilapia aquaculture.

Retraction Note: Possible healing effects of Salvadora persica extract (MISWAK) and laser therapy in a rabbit model of a caustic-induced tongue ulcers: histological, immunohistochemical and biochemical study - Eman Mohamed Faruk; Ola Elsayed Nafea; Hanan Fouad; Usama Fouad Ahmed Ebrahim; Rehab Abd Allah Hasan (Journal of Molecular Histology, 2025)

The impact of betalains and organic selenium on the physiological responses, blood metabolites, redox status, and semen quality of heat-stressed rabbits - Tharwat A. Imbabi; Eman H. Halawa; Elsayed M. Younis; Abdel-Wahab A. Abdel-Warith; Dina A. Selim; Mohamed H. Abdel Aal; Lamiaa M.M. EL-Maghraby; Abdalla El-Hadary; Shimaa A. Amer; Simon J. Davies; Mohamed S. Basiouny; Mahmoud Sitohy; et al. (Animal Feed Science and Technology, 2025)

A Prospective Approach for Screening of Potential Evolution of Aflatoxins in Fish and Fish Feed: Molecular and Afla Fluorometry Assays - Nada H. Eidaroos; Abdelazeem M. Algammal; Mahmoud Mabrok; Mamdouh Y. Elgendy; Mahmoud E. Elsayed; Eman M. El-Diasty; Sara M. El-khamisy; Reham M. El-Tarabili (Current Microbiology, 2025)

Efficacy of curcumin-selenium nanoemulsion in alleviating oxidative damage induced by aluminum chloride in a rat model of Alzheimer’s disease - Safaa M. Awad; Yasser A. Attia; Hassan ElSayed; Shams H. Abdelhafez; Akaber T. Keshta; Eman Rashad; Heba M. A. Khalil; Aziza T. Fathy (Journal of Molecular Histology, 2025)

Vinpocetine and Lactobacillus Attenuated Rotenone-Induced Parkinson’s Disease and Restored Dopamine Synthesis in Rats through Modulation of Oxidative Stress, Neuroinflammation, and Lewy Bodies Inclusion - Hanan M. Hassan; Hadeer O. Abou-Hany; Ahmed Shata; Doaa Hellal; Ahmed M. El-Baz; Zeinab H. ElSaid; Amira A. Haleem; Nesreen Elsayed Morsy; Rawan M. Abozied; Bassant M. Elbrolosy; Sally Negm; Attalla F. El-kott; et al. (Journal of Neuroimmune Pharmacology, 2025)

Low stress drop and strike-slip detachment faulting: insights from a new earthquake sequence in the El-Nuqra Region, Southeastern Desert, Egypt - Hamada Saadalla; Saleh Qaysi; Abdelnasser Mohamed; Elsayed Issawy; Lucia Fojtikova; Eman Abu-Nadr; Ashraf Adly; Mohamed Ezzalarab (Modeling Earth Systems and Environment, 2025)

Administration of melatonin nanoparticles improves testicular blood flow, echotexture of testicular parenchyma, scrotal circumference, and levels of estradiol and nitric oxide in prepubertal ossimi rams under summer heat stress - Eman Fayez; Haney Samir; Fady Sayed Youssef; Ali Salama; Mohamed AI ElSayed (Veterinary Research Communications, 2024)
Environmental heat stress (HS) impairs reproductive efficiency in farm animals. This study investigated, for the first time, how the melatonin and melatonin nanoparticles treatment affected the testicular hemodynamics, testicular volume, echotexture [Pixel intensity (PIX) and integrated density (IND)], scrotal circumference, serum concentration of testosterone (T), estradiol (E 2 ), nitric oxide (NO), and total antioxidant capacity (TAC) in prepubertal Ossimi ram lambs in hot climatic conditions. The lambs undergoing examination had a temperature humidity index (THI) of 87.05 ± 1.70, indicating severe HS condition. Fifteen prepubertal Ossimi ram lambs were exposed to a single s.c injection of either nano melatonin (nano melatonin group; 20 mg/ram; n = 5) or melatonin suspended in two ml of corn oil (melatonin group; 40 mg/ram; n = 5) or two ml of corn oil (control group; n = 5). Blood collection and ultrasonographic assessment of the testes and supratesticular arteries (STAs) were conducted immediately before treatment (W0) and once weekly for six successive weeks after nano melatonin and melatonin injection (W1-W6). Results revealed decreases ( P < 0.05) in the Doppler indices (resistive index; RI and pulsatility index; PI) of the testicular arteries at most time points of the study in the nano melatonin and melatonin groups. PIX of testicular parenchyma was significantly increased (P ˂ 0.05) in the treated groups compared to the control one. IND of testicular parenchyma increased significantly in the nano melatonin group compared to the melatonin and control groups. Testicular volume and scrotal circumference significantly increased ( P < 0.05) in nano melatonin and melatonin groups compared to the control one. T concentration did not significantly ( P > 0.05) change in the treated groups compared to the control group. E 2 , NO, and TAC concentrations increased ( P < 0.05) in the treated groups compared to the control one. In conclusion, this study extrapolated that administrations of melatonin or nano melatonin can ameliorate the effects of environmental HS in prepubertal Ossimi ram lambs with a more protective effect and lower dose of nano melatonin.

Promoting effect of sunset yellow on N-methyl N-nitrosourea-induced rat mammary carcinogenesis: Implications of molecular mechanisms - Elsayed I. Salim; Malak I. Elbassuny; Magdy E. Mahfouz; Eman M. El Nashar; Maha A. Alghamdi; Mohammad El-Nablaway; Hend M. Selim (Toxicology Letters, 2024)

Hexaflumuron insecticide exposure induces behavior alterations, hemato-biochemical disorders, antioxidant-immune dysfunction, and histopathological alterations in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Moustafa M. S. Fouda; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Basma A. Elshafey; Simon J. Davies; Afaf N. Abdel Rahman (Veterinary Research Communications, 2024)

Rosuvastatin repurposing for prophylaxis against ethanol-induced acute gastric ulceration in rats: a biochemical, histological, and ultrastructural perspective - Hanan I. El-kerdasy; Eman Mohamed Faruk; Dina Allam Abdelmaksoud Hassan; Ola Elsayed Nafea; Fatma Ibrahim; Rania Abubaker Bagabir; Hala Magdy Anwer; Amany M. Allam (Inflammopharmacology, 2024)

Quantitative analysis of residual butylated hydroxytoluene and butylated hydroxyanisole in Salmo salar, milk, and butter by liquid chromatography–tandem mass spectrometry - Sara Abdel Basset Galal; Mohammad Madhat Mousa; Eman Saad Elzanfaly; Emad Mohamed Hussien; Enas Abdel Hakim Amer; Hala Elsayed Zaazaa (Food Chemistry, 2024)

Angiotensin II Type 1 receptor blockade attenuates the neuropathological changes in the spinal cords of diabetic rats with modulation of nuclear factor erythroid 2-related factor 2/ heme oxygenase 1 system - Hassan Reda Hassan Elsayed; Eyad Mohamed Tolba Ali; Mohammed Rami Rabei; Eman Mohamad El Nashar; Mansour Abdullah Alghamdi; Norah Saeed Al-Zahrani; Shaker Hassan Alshehri; Rashid A. Aldahhan; Amira Ibrahim Morsy (Tissue and Cell, 2024)

The Influence of Lactobacillus spp. Secondary Metabolites Isolated from Immature Egyptian Honey on Human Pathogens, Transcription of Virulence Genes and Lung Cancer - Tarek R. Elsayed; Eman Nour; Ahmed A. Hamed; Ashwak Abdel-Moneim Hassan; Yasser Essam Elenany (Indian Journal of Microbiology, 2024)
This work aimed to isolate, and identify Lactic Acid Bacteria LAB from Egyptian immature citrus honey, and characterize their secondary metabolites, as well as determine the antibacterial activities and transcription of virulence genes (stx1, stx2, and eae) influenced by these bacterial secondary metabolites. From twenty hives, twenty immature citrus bee honey samples were taken. Traditional cultural and biochemical testing were used, followed by molecular confirmation. Further, LAB isolates' antibacterial and cytotoxic properties were investigated. 16S rRNA gene sequencing were assessed and, two lactic acid bacterial isolates were identified as Lactobacillus acidophilus Ch 2 and Levilactobacillus brevis Ch 1 . Both isolates have good antagonistic action against clinical pathogens, with Levilactobacillus brevis Ch 1 exhibiting the best antibacterial activity against all indicator pathogens examined. When compared to untreated cancer cells, the isolates demonstrated significant cytotoxic activity. Ch 1 and Ch 2 cell viability percentages were 39.5% and 18.76%, respectively. Furthermore, when exposed to Levilactobacillus brevis Ch 1 metabolites, Shiga-producing Escherichia coli (STEC) virulence gene expression was suppressed. To identify bacterial secondary metabolites, a high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (HPLC-QTOF) approach was developed. Twenty-seven metabolites from diverse chemical classes were discovered in the crude extracts with antibacterial and anticancer characteristics. This is the first thorough investigation on the metabolic profile of LAB isolated from immature Egyptian honey and the findings suggested that isolates or their secondary metabolites could be used in the food sector as medicinal alternatives or as a biocontrol agent.

Narcissus pseudonarcissus L. (Amaryllidaceae) bulb metabolite profiling and biological activities - Youstina Refaat Boshra; Eman Zekry Attia; Ahmed G. Darwish; Maria Refaat Boshra; Mohamed N. Amin; Ashraf Nageeb Elsayed Hamed; Samar Yehia Desoukey; John Refaat Fahim (South African Journal of Botany, 2023)

Antitumor effect of trimetazidine in a model of solid Ehrlich carcinoma is mediated by inhibition of glycolytic pathway and AKT signaling - Reem M. Hazem; Rasha F. Aboslema; Eman T. Mehanna; Safaa M. Kishk; Mohammed Elsayed; Norhan M. El-Sayed (Chemico-Biological Interactions, 2023)

Acute mancozeb-fungicide exposure induces neuro-ethology disruption, health disorders, and immune-oxidative dysfunction in Nile tilapia (Oreochromis niloticus) - Rowida E. Ibrahim; Mohamed A. Elbealy; Gamal A. Salem; Abdelwahab A. Abdelwarith; Elsayed M. Younis; Eman Wagih; Ahmed Asaid Elkady; Simon J. Davies; Afaf N. Abdel Rahman (Aquatic Toxicology, 2023)

Correction to: Possible healing effects of Salvadora persica extract (MISWAK) and laser therapy in a rabbit model of a caustic-induced tongue ulcers: histological, immunohistochemical and biochemical study - Eman Mohamed Faruk; Ola Elsayed Nafea; Hanan Fouad; Usama Fouad Ahmed Ebrahim; Rehab Abd Allah Hasan (Journal of Molecular Histology, 2023)

Hesperidin hexosomal loaded nanodispersion: insights of its antimycobacterial, cytotoxic and anti-HCoV effects - Eman M. Abd Elghani; Farghaly A. Omar; Marwa M. Abdel-Aziz Emam; Abdulaziz M. Al-Mahallawi; Soad H. Tadros; Fathy M. Soliman; Abeer M. ElSayed (Natural Product Research, 2023)

Hospital and laboratory outcomes of patients with COVID-19 who received vitamin D supplementation: a systematic review and meta-analysis of randomized controlled trials - Mohamed Sayed Zaazouee; Mahmoud Eleisawy; Amira M. Abdalalaziz; Mahmoud M. Elhady; Omar Adel Ali; Taghreed Mohamed Abdelbari; Sara Mohamed Hasan; Hossam Waleed Almadhoon; Alaa Yehia Ahmed; Alaa Shaban Fassad; Rewan Elgendy; Eman Adnan Abdel-Baset; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19) has a wide-ranging spectrum of clinical symptoms, from asymptomatic/mild to severe. Recent research indicates that, among several factors, a low vitamin D level is a modifiable risk factor for COVID-19 patients. This study aims to evaluate the effect of vitamin D on hospital and laboratory outcomes of patients with COVID-19. Five databases (PubMed, Embase, Scopus, Web of Science, and Cochrane Library) and clinicaltrials.gov were searched until July 2022, using relevant keywords/Mesh terms. Only randomized clinical trials (RCTs) that addressed the topic were included. The Cochrane tool was used to assess the studies’ risk of bias, and the data were analyzed using the review manager (RevMan 5.4). We included nine RCTs with 1586 confirmed COVID-19 patients. Vitamin D group showed a significant reduction of intensive care unit (ICU) admission (risk ratio = 0.59, 95% confidence interval (CI) [0.41, 0.84], P = 0.003), and higher change in vitamin D level (standardized mean difference = 2.27, 95% CI [2.08, 2.47], P < 0.00001) compared to the control group. Other studied hospital and laboratory outcomes showed non-significant difference between vitamin D and the control group ( P ≥ 0.05). In conclusion, vitamin D reduced the risk of ICU admission and showed superiority in changing vitamin D level compared to the control group. However, other outcomes showed no difference between the two groups. More RCTs are needed to confirm these results.

How can imported monkeypox break the borders? A rapid systematic review - Ramy Mohamed Ghazy; Elsayed Mohamed Hammad; Mohamed Ashraf Hall; Amira Mahboob; Sally Zeina; Eman H. Elbanna; Noha Fadl; Shaimaa Abdelaziz Abdelmoneim; Rony ElMakhzangy; Hammad Mohamed Hammad; Afrah humidan Suliman; Hayat Hasab Alkreem Atia; et al. (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Ameliorative effect of flavocoxid on cyclophosphamide-induced cardio and neurotoxicity via targeting the GM-CSF/NF-κB signaling pathway - Fatma F. Elsayed; Waad M. Elshenawy; Eman M. Khalifa; Mohamed R. Rizq; Rania R. Abdelaziz (Environmental Science and Pollution Research, 2022)
Cyclophosphamide (Cyclo) is a chemotherapeutic agent used as an immunosuppressant and as a treatment for many cancerous diseases. Many previous pieces of literature proved the marked cardio and neurotoxicity of the drug. Thus, this research provides evidence on the alleviative effect of flavocoxid on the cardiac and brain toxicity of cyclophosphamide in mice and determines its underlying mechanisms. Flavocoxid (Flavo) is a potent antioxidant and anti-inflammatory agent that inhibits the peroxidase activity of cyclooxygenase (COX-1 and COX-2) enzymes and 5-lipooxygenase ( 5-LOX ). Flavo was administered orally (20 mg/kg) for 2 weeks, followed by Cyclo (100 mg/kg, i.p.) on day 14. Higher heart and brain weight indices, serum lactate dehydrogenase (LDH), creatine kinase (CK-MB), and nitric oxide (NO) were mitigated following Flavo administration. Flavo modulated oxidative stress biomarkers (malonaldehyde (MDA), glutathione (GSH), and superoxide dismutase (SOD)), tumor necrosis factor-α (TNF - α), and interleukin (IL)-1β. Additionally, cardiac troponin I (cTn-I), nuclear factor kappa B (NF-κB), brain amyloid precursor protein (APP), and granulocyte macrophage colony-stimulating factor (GM-CSF) were decreased by Flavo administration. Moreover, Flavo ameliorated heart and brain histopathological changes and caspase-3 levels. Collectively, Flavo (20 mg/kg) for 14 days showed significant cardio and neuroprotective effects due to its antioxidant, anti-inflammatory, and antiapoptotic activities via modulation of oxidative stress, inflammation, and the GM-CSF/NF-κB signaling pathway.

LC-MS-based identification of bioactive compounds and hepatoprotective and nephroprotective activities of Bignonia binata leaves against carbon tetrachloride-induced injury in rats - Mamdouh Nabil Samy; Ashraf Nageeb Elsayed Hamed; Basma Khalaf Mahmoud; Eman Zekry Attia; Usama Ramadan Abdelmohsen; Michael Atef Fawzy; Mina Ezzat Attya; Mohamed Salah Kamel (Natural Product Research, 2022)

Metabolomic profiling and biological investigation of Tabebuia Aurea (Silva Manso) leaves, family Bignoniaceae - Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Mamdouh Nabil Samy; Usama Ramadan Abdelmohsen; Eman Zekry Attia; Michael Atef Fawzy; Rana Hosny Refaey; Mohammad Alaraby Salem; Sheila Marie Pimentel-Elardo; Justin R. Nodwell; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Long-term exposure to p-Nitrophenol induces hepatotoxicity via accelerating apoptosis and glycogen accumulation in male Japanese quails - Eman A. Ahmed; Howayda E. Khaled; Ahmed K. Elsayed (Environmental Science and Pollution Research, 2021)

Whole-genome sequencing of Egyptian multidrug-resistant Klebsiella pneumoniae isolates: a multi-center pilot study - May Sherif; Mattia Palmieri; Caroline Mirande; Hadir El-Mahallawy; Hebatallah G. Rashed; Fadwa Abd-El-Reheem; Arwa Ramadan El-Manakhly; Radwa Ahmad Rabea Abdel-latif; Aliaa Gamaleldin Aboulela; Laila Yosef Saeed; Soheir Abdel-Rahman; Eman Elsayed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Two-stage cultivation of Chlorella vulgaris using light and salt stress conditions for simultaneous production of lipid, carotenoids, and antioxidants - Hamdy Elsayed Ahmed Ali; Eman A. El-fayoumy; Wessam E. Rasmy; Ramadan M. Soliman; Mohd Azmuddin Abdullah (Journal of Applied Phycology, 2021)

RETRACTED ARTICLE: Possible healing effects of Salvadora persica extract (MISWAK) and laser therapy in a rabbit model of a caustic-induced tongue ulcers: histological, immunohistochemical and biochemical study - Eman Mohamed Faruk; Ola Elsayed Nafea; Hanan Fouad; Usama Fouad Ahmed Ebrahim; Rehab Abd Allah Hasan (Journal of Molecular Histology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Impact of Soil Biochar Incorporation on the Uptake of Heavy Metals Present in Wastewater by Spinach Plants - Christopher Nzediegwu; Shiv Prasher; Eman Elsayed; Jaskaran Dhiman; Ali Mawof; Ramanbhai Patel (Water, Air, & Soil Pollution, 2020)

Effect of Biochar on the Yield of Potatoes Cultivated Under Wastewater Irrigation for Two Seasons - Christopher Nzediegwu; Shiv Prasher; Eman Elsayed; Jaskaran Dhiman; Ali Mawof; Ramanbhai Patel (Journal of Soil Science and Plant Nutrition, 2019)

A comparative study on the possible protective effect of esomeprazole, spirulina, wheatgrass on indomethacin-induced gastric ulcer in male albino rats - Amy Fakhry Boushra; Asmaa Mohammed Elsayed; Noha Abdellatif Ibrahim; Maha Khaled Abdelwahed; Eman Ibrahim Ahmed (Molecular Biology Reports, 2019)

A preliminary study of the relation between IL-4 and hypertension in type II diabetes mellitus - Eman Badr; Mohamed Assar; Elsayed I. Elshayeb; Safaa Fath El-Bab; Salah El-kousy (Molecular Biology Reports, 2018)

Association of Tumor Necrosis Factor Alpha-Induced Protein 3 Interacting Protein 1 (TNIP1) Gene Polymorphism (rs7708392) with Lupus Nephritis in Egyptian Patients - Mohamed Moustafa Rizk; Eman Tayae Elsayed; Ahmed Fathi ElKeraie; Ireny Ramzy (Biochemical Genetics, 2018)

Immunological role of CD4+CD28null T lymphocytes, natural killer cells, and interferon-gamma in pediatric patients with sickle cell disease: relation to disease severity and response to therapy - Mohsen Saleh ElAlfy; Amira Abdel Moneam Adly; Fatma Soliman ElSayed Ebeid; Deena Samir Eissa; Eman Abdel Rahman Ismail; Yasser Hassan Mohammed; Manar Elsayed Ahmed; Aya Sayed Saad (Immunologic Research, 2018)

Association of genetic variants of pentraxin 3 rs3816527 with hypertension in Chronic kidney disease patients - Eman A. E. Badr; Ghada E. Hamoda; Safaa I. Tayel; Elsayed I. Elshayeb (Molecular and Cellular Biochemistry, 2017)

Sorption/desorption behavior of oxytetracycline and sulfachloropyridazine in the soil water surfactant system - Eman M. ElSayed; Shiv O. Prasher (Environmental Science and Pollution Research, 2014)

Tranilast ameliorates impaired hepatic functions in Schistosoma mansoni-infected mice - Eman Said; Shehta A. Said; Wagdi F. Elkashef; Nariman M. Gameil; Elsayed M. Ammar (Inflammopharmacology, 2012)